Assessment of the risk factors, depression and quality of life in epileptic patients: a prospective study - Rama Rao, Tadikonda; Sharmeen, Hafsa; Tabassum, Afshaan; Jasmine, Sena Jessy (International Journal Of Community Medicine And Public Health, 2025)
Background: Assessing depression and quality of life in epileptic patients is crucial due to epilepsy's neurological and psychological effects. This study examines depression prevalence and severity highlighting the burden on patients and its effect on quality of life, emphasizing the importance of thorough clinical evaluations for effective management. Methods: A six-month prospective observational study included 120 patients from the inpatient general medicine department. Depression was assessed by patient health questionnaire-9 and quality of life in epilepsy-10 inventory was used to assess quality of life. Statistical analysis was performed using descriptive statistics, the chi-square test, and the Wilcoxon Rank-Sum test. Results: The severity of depression assessed, revealed that 13.3% experienced minimal, 35.8% had mild, 30% showed moderate, 14.2% had moderately severe, and 6.7% were severe depression. Females exhibited higher depression rates (55.7%) compared to males (44.3%). Highest depression rates were found in patients aged 31-40 (44.3%). Monotherapy was slightly associated with higher depression rates (54.1%) than polytherapy (45.9%). Chi-square analysis indicated a significant association between depression and quality of life (p=0.033*). The Wilcoxon Rank-Sum test showed substantial differences in Epilepsy Effects, Role Functioning, and Mental Health domains between depressed and non-depressed patients, with p-values of 0.019*, 0.017*, and 0.146*, respectively. Conclusions: The study highlights the need to address depression in epilepsy patients due to its significant impact on mental well-being and overall quality of life. Effective management should consider both neurological and psychological aspects for optimal patient care.